News Mining And Tecnical Analysis For Stock Market Prediction - Nikfarjam, Azadeh (2010)
In this research we proposed and evaluated a new method in stock market price trend. We trained a classifier which is able to classify any incoming news into three final categories based on their short term impact on market trend. In order to analyze the news content, we proposed a new method in text classification which uses semantic relations between news article words.